RTG-loaded nanomicelles (CS–VES–NAC) for oral anti-HIV drug delivery. Issue 79 (10th August 2016) - Hu, Liming; Wu, Jiazhou; Li, Zhipeng; Bu, Ming; Qiao, Shenglin; Wang, Hao
Abstract : An acetylcysteine–chitosan–vitamin E succinate copolymer (CVN) was synthesized from chitosan (CS), vitamin E succinate (VES) and N -acetyl-l -cysteine (NAC) as self-assembled nanomicelles for multifunctional delivery of anti-HIV drug Raltegravir (RTG). Abstract : An acetylcysteine–chitosan–vitamin E succinate copolymer (CVN) was synthesized from chitosan (CS), vitamin E succinate (VES) and N -acetyl-l -cysteine (NAC) as self-assembled nanomicelles for multifunctional delivery of anti-HIV drug Raltegravir (RTG). The chemical structure of the copolymer was determined by FT-IR and 1 H NMR and the molecular weight was tested by Ubbelohde Viscometer. RGT-loaded polymer nanomicelles were prepared using a probe ultrasonic method. Their physiochemical characteristics, e.g. morphology and nanoparticle size distribution were evaluated by means of transmission electron microscopy (TEM) and dynamic light scattering (DLS). The RGT-loaded nanoparticles assumed a spherical shape and have unimodal size distribution. It was found that CVN copolymer and various amounts of RTG could self-assemble to form nanomicelles in sizes ranging from 187.3 nm to 205.2 nm, and their polydispersity indexes (PDI) were under 0.3. The new type of CVN nanomicelles showed attractive self-assembly characteristics, stability, good cytocompatibility, and high loading capacity for RTG. The cytotoxicity assay and cell inhibitory activity tests of RGT-loaded nanomicells were carried out and the RTG-loaded nanomicelles showed comparable inhibitory efficacy with the free drug.